Dental implants in growing children - S K Mishra; N Chowdhary; R Chowdhary (Wolters Kluwer Medknow Publications, 2013)
The replacement of teeth by implants is usually restricted to patients with completed craniofacial growth. The aim of this literature review is to discuss the use of dental implants in normal growing patients and in patients with ectodermal dysplasia and the influence of maxillary and mandibular skeletal and dental growth on the stability of those implants. It is recommended that while deciding the optimal individual time point of implant insertion, the status of skeletal growth, the degree of hypodontia, and extension of related psychological stress should be taken into account, in addition to the status of existing dentition and dental compliance of a pediatric patient.